Implementation of the Yanbu’a Method in Improving Students’ Ability to Read the Qur’an - Nada Salsabillah; Muhammad Endy Fadlullah; Nasrodin Nasrodin (JURNAL ISLAM NUSANTARA, 2025)
The persistent gap between curriculum demands and students’ foundational competence in Qur’anic reading in formal Islamic secondary schools highlights the urgent need for effective, time-efficient instructional approaches. This study aims to analyze the effectiveness and practical implementation of the Yanbu’a method in improving students’ Qur’anic reading ability in contexts with limited instructional time. The growing gap between curricular demands and students’ foundational Qur’anic literacy necessitates pedagogical strategies that are both systematic and adaptable. In many madrasahs, conventional recitation approaches remain dominant despite varying student readiness levels and time constraints. This research employed a qualitative case study design. Data were collected through participatory classroom observations at the Ula, Wustho, and Ulya levels; in-depth interviews with the madrasah principal, three teachers, and three students; and analysis of instructional guidelines and learning records. The findings indicate that structured student grouping strengthened instructional differentiation and learning focus. Continuous teacher training enhanced pedagogical consistency and classroom management. The integration of motivational strategies and adaptive learning media increased student engagement and practice intensity. Formative evaluation based on mastery learning ensured gradual improvement in reading accuracy and fluency. The Yanbu’a method fostered disciplined learning routines and measurable progress across levels. This study contributes empirical evidence supporting the contextual adaptability of the Yanbu’a method in formal madrasah settings and recommends institutionalized teacher training and time-efficient instructional planning to sustain learning outcomes.